Causal attributions of success and failure made by undergraduate students in an introductory-level computer programming course - Hawi, Nazir (Computers and education, 2010)
The purpose of this research is to identify the causal attributions of business computing students in an introductory computer programming course, in the computer science department at Notre Dame University, Louaize. Forty-five male and female undergraduates who completed the computer programming course that extended for a 13-week semester participated. Narrative interviews were conducted to obtain their perceptions. While some research confirmed that the four most responsible causes for success and failure in achievement contexts are ability, effort, task difficulty, and luck, this research shows that in its context ‘ability’ and ‘luck’ were absent, and ‘task difficulty’ and ‘effort’ were almost absent. In all, participants made 10 causal attributions that were either cultural or specific to computer programming. The 10 causal attributions are ‘learning strategy’, ‘lack of study’, ‘lack of practice’, ‘subject difficulty’, ‘lack of effort’, ‘appropriate teaching method’, ‘exam anxiety’, ‘cheating’, ‘lack of time’, and ‘unfair treatment’. All high achievers cited appropriate ‘learning strategy’.